The Effect of Winter Mountaineering Training on Athlete Success and Permanency of Learning - Burak Kural; Selami Yüksek; Vedat Ayan (Journal of Educational Issues, 2024)
Introduction and Purpose: The aim of this research is to examine the effects of athlete success and permanency of learning the winter mountaineering training given by the Turkish Mountaineering Federation. The research group consists of a total of 105 participants, 21 women (20%) and 84 men (80%) who attended the winter mountaineering training course organized by the Turkish Mountaineering Federation. Materials and Methods: In this study, quasi-experimental design was used in the research. A multiple-choice achievement test of 25 questions which includes knowledge and practice issues related to winter mountaineering education was prepared. The reliability analysis of the achievement test was made with the “ITEMAN” program. The pre-test-post-test data of the study were collected on 20-27 January 2019 on Zigana Mountain, and 4 weeks later, the permanency test data was collected on 28 February 2019 on Erciyes Mountain. In data analysis, for correlated samples (repeated measures) one-factor ANOVA and for repeated measurements two-factor ANOVA analyzes were performed. Findings: There was a significant difference between the pre-test-post-tests-permanency test total, knowledge, and application scores of the athletes. It is seen that the achievement scores of male and female athletes before and after the training do not differ significantly. Results: According to the research results; It has seen that the winter mountaineering training given by the Turkish mountaineering federation has a positive effect on the knowledge and practice levels of the athletes and has an important contribution in the context of the permanency of learning. In addition, it was determined that the success scores of female athletes who received training were higher than male athletes.